Water conservation policies, practices and future options in Palestine: a special focus on agriculture - Nofal I.; Rabi A.; Dudeen B. (Harmonization and integration of water saving options. Convention and promotion of water saving policies and guidelines, 2007)
Palestinian Authority Territories represented in the West Bank and Gaza Strip has an acute water stress since the allocated water per capita per year is 70 m3. Agricultural sector plays a crucial role in the social well being of the Palestinian people due to the fact that it is considered for a lot of people the main source of their living, and to others, it is considered as an additional income because they can save nutritional materials. Total current water use in the West Bank and Gaza Strip (WBGS) is estimated to be about 286 million cubic meters (MCM) per year. Agriculture continues to be the largest consumer of water accounting for more than 60 percent of total use (167 MCM, about half each in the West Bank and in the Gaza Strip). Groundwater wells constitute the only source of irrigation water in the Gaza Strip. In the West Bank, wells and springs contribute almost equal amounts of irrigation water, though the vast majority of springs are concentrated in the Jordan Valley (Jericho District). This critical situation related to water resources in Palestine motivated Palestinian National Authority (PNA) in cooperation with national and international bodies to set the required policies for water conservation and design the possible future options for water use. This paper addressed in brief the following: Water resources budget, water use, agricultural water demand, and the base of water policy, main water supply policy elements, agricultural policy objective, existing water conservation practices and proposed practices.
5. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2006/05/03-07, Malta (Malta)